2013
DOI: 10.1016/j.rgg.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Petrochemical characteristics of carbonaceous shales in the eastern Bureya massif and their precious-metal mineralization

Abstract: Some geological, petrochemical, and geochemical characteristics of carbonaceous shales as a new unconventional natural source of gold and PGE are considered by the example of the Kimkan and Sutyr’ units of the Bureya massif (southern Far East, Russia). It is shown that shales of the units belong to the terrigenous-carbonaceous and siliceous-carbonaceous formations. They accumulated in deep-water trenches, and the active continental margin was probably their main provenance. The carbonaceous terrigenous-sedimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Several studies have shown that the chemical compositions of clastic rocks are significantly controlled by plate tectonic settings of their provenances, and consequently clastic rocks from different tectonic settings possess terrain-specific geochemical signatures (Bhatia 1983;Roser and Korsch 1988). Roser and Korsch (1988) used major oxides as variables and established major element discriminant functions to discriminate four major provenances field namely felsic, mafic, intermediate and quartzose recycled, which are frequently used by many researchers to identify the provenance of terrigenous sediments (Hofer et al 2013;Khanchuk et al 2013;Vdacny et al 2013) and to reflect the source rock composition (Shadan and Hosseini-Barzi 2013).…”
Section: Provenancementioning
confidence: 99%
“…Several studies have shown that the chemical compositions of clastic rocks are significantly controlled by plate tectonic settings of their provenances, and consequently clastic rocks from different tectonic settings possess terrain-specific geochemical signatures (Bhatia 1983;Roser and Korsch 1988). Roser and Korsch (1988) used major oxides as variables and established major element discriminant functions to discriminate four major provenances field namely felsic, mafic, intermediate and quartzose recycled, which are frequently used by many researchers to identify the provenance of terrigenous sediments (Hofer et al 2013;Khanchuk et al 2013;Vdacny et al 2013) and to reflect the source rock composition (Shadan and Hosseini-Barzi 2013).…”
Section: Provenancementioning
confidence: 99%
“…The relatively high values of ultrastable minerals in these provinces is probably due to the large distance of transport and the abundance of clastic sediments in the hinterland as well as the effect of physical marine processes such as waves and currents along the coastal area. The major-element-based provenance discriminant function diagram of Roser and Korsch (1988) is frequently used by many researchers to identify the provenance of terrigenous sediments (Hofer et al, 2013;Khanchuk et al, 2013;Vdačný et al, 2013) and to reflect the source rock composition (Shadan and Hosseini-Barzi, 2013). This discriminant function diagram reveals that the source sediments of the Hawkesbury Sandstone were mature polycyclic continental sedimentary rocks, supporting the interpretation that they were derived from a granitic-gneissic or sedimentary source area ( Figure 9a), and similar to a passive margin-derived source (Roser and Korsch, 1986;Bhatia, 1983).…”
Section: Provenancementioning
confidence: 99%
“…The major-element-based provenance discriminant function diagram of Roser and Korsch (1988) is frequently used by many researchers to identify the provenance of terrigenous sediments (Hofer et al, 2013;Khanchuk et al, 2013;Vdačný et al, 2013) and to reflect the source rock composition (Shadan and Hosseini-Barzi, 2013). This discriminant function diagram reveals that the source sediments of the Hawkesbury Sandstone were mature polycyclic continental sedimentary rocks, supporting the interpretation that they were derived from a granitic-gneissic or sedimentary source area (Figure 9a), and similar to a passive margin-derived source (Roser and Korsch, 1986;Bhatia, 1983).…”
Section: Provenancementioning
confidence: 99%